Vitamin D deficiency decreases survival of bacterial meningoencephalitis in mice. Issue 1 (December 2015) - Djukic, Marija; Sostmann, Nadine; Bertsch, Thomas; Mecke, Marianne; Nessler, Stefan; Manig, Anja; Hanisch, Uwe-Karsten; Triebel, Jakob; Bollheimer, L; Sieber, Cornel; Nau, Roland
Abstract Background Meningoencephalitis caused byEscherichia coli is associated with high rates of mortality and risk of neurological sequelae in newborns and infants and in older or immunocompromised adults. A high prevalence of neurological disorders has been observed in geriatric populations at risk of hypovitaminosis D. Methods In vivo, we studied the effects of vitamin D3 on survival and the host's immune response in experimental bacterial meningoencephalitis in mice after intracerebralE. coli infection. To produce different systemic vitamin D3 concentrations, mice received a low, standard, or high dietary vitamin D3 supplementation. Bacterial titers in blood, spleen, and brain homogenates were determined. Leukocyte infiltration was assessed by histological scores, and tissue cytokine or chemokine concentrations were measured. Results Mice fed a diet with low vitamin D3 concentration died earlier than control animals after intracerebral infection. Vitamin D deficiency did not inhibit leukocyte recruitment into the subarachnoid space and did not lead to an increased density of bacteria in blood, spleen, or brain homogenates. The release of proinflammatory interleukin (IL)-6 was decreased and the release of anti-inflammatory IL-10 was increased in mice fed a diet with high vitamin D3 supplementation. Conclusion Our observations suggest a detrimental role of vitamin D deficiency in bacterial central nervous system infections. Vitamin D may exert immune regulatory functions.